2014
DOI: 10.1016/j.neuron.2013.12.013
|View full text |Cite|
|
Sign up to set email alerts
|

Neuronal Machinery of Sleep Homeostasis in Drosophila

Abstract: SummarySleep is under homeostatic control, but the mechanisms that sense sleep need and correct sleep deficits remain unknown. Here, we report that sleep-promoting neurons with projections to the dorsal fan-shaped body (FB) form the output arm of Drosophila’s sleep homeostat. Homeostatic sleep control requires the Rho-GTPase-activating protein encoded by the crossveinless-c (cv-c) gene in order to transduce sleep pressure into increased electrical excitability of dorsal FB neurons. cv-c mutants exhibit decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
208
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 245 publications
(234 citation statements)
references
References 84 publications
12
208
1
Order By: Relevance
“…dFB neurons in sleep-deprived flies tend to be electrically active, with high input resistances and long membrane time constants, while neurons in rested flies tend to be electrically silent3. Correlative evidence thus supports the simple view that homeostatic sleep control works by switching sleep-promoting neurons between active and quiescent states3. Here we demonstrate state switching by dFB neurons, identify dopamine as a neuromodulator that operates the switch, and delineate the switching mechanism.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…dFB neurons in sleep-deprived flies tend to be electrically active, with high input resistances and long membrane time constants, while neurons in rested flies tend to be electrically silent3. Correlative evidence thus supports the simple view that homeostatic sleep control works by switching sleep-promoting neurons between active and quiescent states3. Here we demonstrate state switching by dFB neurons, identify dopamine as a neuromodulator that operates the switch, and delineate the switching mechanism.…”
supporting
confidence: 68%
“…4a). The biophysical properties of single dFB neurons, recorded in the same individual before and after operating the dopamine switch, varied as widely as those in sleep-deprived and rested flies3.…”
mentioning
confidence: 99%
“…Similar to flies undergoing mechanical nighttime sleep deprivation, these flies exhibited a significant increase in Aβ accumulation, compared to controls (Figures 3A and 3D). It was previously shown that the ExFl2 fan-shaped body (FB) neurons promote sleep [36, 37], and we recently identified a restricted Gal4 driver ( R72G06-Gal4 ) from the Rubin/Janelia Farm collection that contains these cells (data not shown). Thus, in order to address whether increasing sleep would cause the opposite phenotype, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Our data support this hypothesis, as sleep deprivation in flies leads to hyperexcitability of l-LNv neurons. Another recent study found that the ExFl2 neurons in Drosophila also exhibited increased excitability with sleep deprivation, although in that case, it was suggested that this phenotype was related to the specific sleep-promoting function of those neurons [37]. …”
Section: Discussionmentioning
confidence: 99%
“…Based on the TfAP-2 expression pattern, we hypothesized that TfAP-2 acts in either MB-, sNPF-, Tim- or PDF-expressing neurons. We thus used these tissue-specific Gal4 lines as well as cv - cGal4 driver, which is expressed in known sleep-controlling crossveinless - c neurons [34] to downregulate TfAP - 2 and to monitor sleep behavior. As GABAergic neurons play a role in sleep control, we also tested the gad - Gal4 driver [35].…”
Section: Resultsmentioning
confidence: 99%